Pengaruh Kepercayaan Merek, Produk dan Hargaterhadap Keputusan Pembeli di Toko Indomaret di Pulau Tidore - Lating, Safitri A. (Peneliti.net, 2025)
This study aims to determine the influence of brand trust, products and prices on buyer decisions at Indomaret Store Tidore Island. The research method used in this study is quantitative method. The sample in this study was 384, the sampling technique used was Probabilitiy Sampling, which used the Cochran formula and data collection techniques using questionnaires. The results of this study show that brand trust, product and price simultaneously affect buyer decisions. While partially, only product and price variables have a positive and significant effect on buyer decisions and brand trust variables do not have a significant effect on buyer decisions